2014
DOI: 10.1016/j.jgr.2013.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Red Ginseng-containing diet helps to protect mice and ferrets from the lethal infection by highly pathogenic H5N1 influenza virus

Abstract: The highly pathogenic (HP) H5N1 influenza virus is endemic in many countries and has a great potential for a pandemic in humans. The immune-enhancing prowess of ginseng has been known for millennia. We aimed to study whether mice and ferrets fed with Red Ginseng could be better protected from the lethal infections of HP H5N1 influenza virus than the infected unfed mice and ferrets. We fed mice and ferrets with Red Ginseng prior to when they were infected with HP H5N1 influenza virus. The mice and ferrets fed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Mice inoculated with a lethal dose of virus and ginseng preparations were protected against weight loss with 100% survival rates during primary infection, and they developed immunity against secondary viral infection 395,396 . The use of various ginseng extracts to treat mice infected with influenza virus decreased the interleukin (IL)‐6 and IL‐8 cytokines and increased antiviral cytokine interferon (IFN) upon influenza virus infection 397–400 . It was demonstrated that ginsenosides, particularly Rb1, interact with viral hemagglutinin proteins, preventing the virus from binding to host cells and viral entry into the cytoplasm 401 .…”
Section: Current and Prospective Use Of Adaptogens In Stress‐inducedmentioning
confidence: 99%
“…Mice inoculated with a lethal dose of virus and ginseng preparations were protected against weight loss with 100% survival rates during primary infection, and they developed immunity against secondary viral infection 395,396 . The use of various ginseng extracts to treat mice infected with influenza virus decreased the interleukin (IL)‐6 and IL‐8 cytokines and increased antiviral cytokine interferon (IFN) upon influenza virus infection 397–400 . It was demonstrated that ginsenosides, particularly Rb1, interact with viral hemagglutinin proteins, preventing the virus from binding to host cells and viral entry into the cytoplasm 401 .…”
Section: Current and Prospective Use Of Adaptogens In Stress‐inducedmentioning
confidence: 99%
“…The antiviral effects on the H1N1 strain have been most widely tested, and those on H3N2, H9N2/G1 (avian influenza), and H5N1 were also examined. In detail, RGE has been reported to have antiviral effects on H1N1, H3N2, and H5N1 [31] , [32] ; GP has effects on H1N1 and H3N2 [33] ; and saponin has an effect on H1N1 [34] . The antiviral activities of RGE, GP, and ginseng saponin fraction have also been compared using the H1N1 strain.…”
Section: Influenza Virusmentioning
confidence: 99%
“…KRG was found to have beneficial effects for subjects with acute respiratory diseases in clinical studies, including antiviral properties that specifically alleviate influenza [ [31] , [32] , [33] , [34] , [35] , [36] ]. KRG also significantly reduced the incidence of contracting a cold in one study [ 37 ] and reduced the frequency of contracting acute respiratory diseases in another [ 38 ].…”
Section: Introductionmentioning
confidence: 99%